Spatio-temporal evolution of the COVID-19 across African countries - Naffeti, Bechir; Bourdin, Sebastien; Ben Aribi, Walid; Kebir, Amira; Ben Miled, Slimane (Frontiers in Public Health, 2022)
The aim of this study is to make a comparative study on the reproduction number R_0 computed at the beginning of each wave for African countries and to understand the reasons for the disparities between them. The study covers the two first years of the COVID-19 pandemic and for 30 African countries. It links pandemic variables, reproduction number R_0, demographic variable, median age of the population, economic variables, GDP and CHE per capita, and climatic variables, mean temperature at the beginning of each waves. The results show that the diffusion of COVID-19 in Africa was heterogeneous even between geographical proximal countries. The difference of the basic reproduction number R_0 values is very large between countries and is significantly correlated with economic and climatic variables GDP and temperature and to a less extent with the mean age of the population